Frog and Duck - Velthuijs, Max (Andersen London, 1999)
This is one of two titles introducing Frog and one of his friends. Frog and Duck are out walking. Frog has lots of ideas about what they should do but Duck has the best suggestion of all when he says they should be friends forever